A percepção dos empresários das micro e pequenas panificadoras da cidade de Sobral sobre a implantação das boas práticas de fabricação. - Albuquerque, Luciana Martins (2020)
One of the branches of the company that had a significant growth in the last but decades, it is the food sector. Highlighting the bakery sector and confectionery. Due to rapid urbanization, concentrations in large cities and also to the change in lifestyle, is that the search for for more practical and faster foods (ASSIS et al., 2017).